Spheniodal mucocele causing bilateral optic neuropathy and ophthalmoplegia - Ambika Selvakumar; Balasubramanyam Mahalaxmi; V Ananth; Cugati Gautam (Indian Journal of Ophthalmology, 2014)
Sphenoid sinus mucocele comprises only 2% of all paranasal sinus mucoceles. In literature, there is a case report on sphenoidal mucocele causing bilateral optic neuropathy, with unilateral partial recovery and cranial nerve palsy, but we did not come across any literature with bilateral optic neuropathy and ophthalmoplegia together caused by spheno-ethmoidal mucocele. We present such a rare case of spheno-ethmoidal mucocele causing bilateral optic neuropathy and unilateral sixth nerve palsy who had postsurgery, unilateral good vision recovery, and complete resolution of sixth nerve palsy.